Author Correction: Charles D. Surh 1960–2017. (September 2018) - Nikolich-Žugich, Janko
In the version of this article initially published, the year of birth provided (1960) was incorrect. The correct year is 1961. The error has been corrected in the HTML and PDF versions of the article.